Construction of Islamic Identity of Students in the Digital Era: A Case Study of the Ibnurusyd Campus Da'wah Community - Aan Gunawan; Syahrudin Syahrudin (JISEI: Journal of Islamic Studies and Educational Innovation, 2025)
This study explores the construction of Islamic identity among university students within the Ibnurusyd Campus Da'wah Community in the digital era. Using a qualitative case study approach, the research analyzes how students build their religious identity through both offline and online engagements. Data were collected through participatory observation, in-depth interviews, and document analysis of digital content produced by the community. The findings reveal that identity construction occurs through a combination of spiritual mentoring, digital da'wah strategies, and socio-cultural participation. The community employs integrative, participatory, and reflective da'wah methods while emphasizing religious moderation and digital literacy. Despite challenges such as information fragmentation, declining offline engagement, and limited digital capacity, the digital sphere also offers opportunities for wider outreach and youth empowerment. This study contributes to the discourse on youth religiosity in the digital age and provides a model for contextual Islamic identity formation among students.